Meta Analysis: Effects of Peer, Family, and School Environment on Smoking Behavior in Adolescents - Anse Putra; Hanung Prasetya; Bhisma Murti (Journal of Health Promotion and Behavior, 2023)
Background: Smoking behavior is a behavior that is harmful to health, but there are still many people who do smoking activities, even someone starts smoking starting as a teenager. This study aimed to estimate the influence of peers, family, school on smoking behavior in adolescents through a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This was a systematic review and meta-analysis conducted following the PRISMA diagram and the PICO format. Population: Teenagers. Intervention: Smokers' peers, smokers' family members, schools apply smoking rules. Comparison: Peers don't smoke, family members don't smoke, schools don't enforce smoking rules. Outcome: Smoking. The online databases used are Google Scholar, Science Direct, and ProQuest with the words ''Smoking peers'' AND ''Smoking parents'' AND ''Smoking policy school'' AND ''smoking'' AND behavior AND adolescents AND ''cross sectional'' AND aOR. There were 16 cross-sectional studies published in 2013-2023 that met the inclusion criteria. Analysis was performed with RevMan 5.3. Results: The meta-analysis included 16 cross-sectional studies from India, Korea, China, Hong Kong, Taiwan, South Africa, America, Chile, Denmark, Saudi Arabia and, Turkey. The total sample was 191,101. Smoking behavior increased with smoker peers (aOR= 5.04; 95% CI = 3.23 to 7.87; p< 0.001), smoker family members (aOR=2.04; 95% CI= 1.45 to 2.87; p< 0.001), and low smoking policy in school (aOR= 1.00; 95% CI= 0.65 to 1.54; p< 0.001). Conclusion: There is influence of smoking peers, smoking families, smoking policies in schools with smoking behavior in adolescents. Keywords: adolescents, peers of smokers, families of smokers, smoking policies. Correspondence: Anse Putra. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: anseputra9@gmail.com. Mobile: +6282120298227.